M3FNet: Multi-modal multi-temporal multi-scale data fusion network for tree species composition mapping - Yuwei Cao; Nicholas C. Coops; Brent A. Murray; Ian Sinclair; Robere-McGugan Geordie (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Enhancing tree species composition mapping using Sentinel-2 and multi-seasonal deep learning fusion - Yuwei Cao; Nicholas C. Coops; Brent A. Murray; Ian Sinclair (International Journal of Remote Sensing, 2025)

Factor analysis of multimodal MRI, biofluid, and vascular biomarkers reveals latent constructs of brain health - Ella Rowsthorn; Ming Ann Sim; William T. O’Brien; Stuart J. McDonald; Katherine Franks; Benjamin Sinclair; Trevor T.-J. Chong; Stephanie Yiallourou; Marina Cavuoto; Lucy Vivash; Terence J. O’Brien; Xingfeng Shao; et al. (GeroScience, 2025)
Individual imaging and fluid biomarkers provide insights into specific components of brain health, but integrated multimodal approaches are necessary to capture the complex, interrelated biological systems that contribute to brain homeostasis and neurodegenerative disease. Using data from the Brain and Cognitive Health (BACH) cohort study ( N = 127; mean age = 67 years, 68% women), we performed an exploratory factor analysis to identify latent constructs of brain health. We included multimodal neurovascular imaging markers, brain atrophy metrics, plasma Alzheimer’s disease (AD) biomarkers, and cardiovascular risk factors. Five constructs emerged: “Brain & Vascular Health” (greater hippocampal volume, basal ganglia enlarged perivascular spaces (ePVS), cerebral blood flow, and HDL cholesterol; lower ventricle volume and BMI), “Structural Integrity” (greater cortical thickness, fractional anisotropy, and basal ganglia ePVS), “White Matter (WM) Fluid Dysregulation” (greater WM ePVS and Free Water), “AD Biomarkers” (higher phosphorylated tau [pTau]181 and pTau217; lower amyloid-beta 42/40 ratio), and “Neuronal Injury” (higher glial fibrillary acidic protein and neurofilament light chain). All constructs were associated with age (β = - 0.70–0.39, p ≤ 0.014), except for WM Fluid Dysregulation ( p > 0.05). Brain and Vascular Health and Structural Integrity (partial r = 0.305, p < 0.001) and AD biomarkers and neuronal injury (partial r = 0.248, p = 0.005) were positively correlated. Only Brain and Vascular Health was associated with global cognition (β = 0.27, SE = 0.13, p = 0.043). These findings provide a data-driven framework for examining distinct constructs underlying vascular health, fluid regulation, and neurodegenerative pathology. We demonstrate the utility of using multiple biomarkers to probe these biological systems, paving the way for future research to explore how these systems change across diverse neurodegenerative conditions. Graphical abstract

Guiding principles for rewilding - Steve Carver; Ian Convery; Sally Hawkins; Rene Beyers; Adam Eagle; Zoltan Kun; Erwin Van Maanen; Yue Cao; Mark Fisher; Stephen R. Edwards; Cara Nelson; George D. Gann; et al. (Conservation Biology, 2021)
There has been much recent interest in the concept of rewilding as a tool for nature conservation, but also confusion over the idea, which has limited its utility. We developed a unifying definition and 10 guiding principles for rewilding through a survey of 59 rewilding experts, a summary of key organizations’ rewilding visions, and workshops involving over 100 participants from around the world. The guiding principles convey that rewilding exits on a continuum of scale, connectivity, and level of human influence and aims to restore ecosystem structure and functions to achieve a self‐sustaining autonomous nature. These principles clarify the concept of rewilding and improve its effectiveness as a tool to achieve global conservation targets, including those of the UN Decade on Ecosystem Restoration and post‐2020 Global Biodiversity Framework. Finally, we suggest differences in rewilding perspectives lie largely in the extent to which it is seen as achievable and in specific interventions. An understanding of the context of rewilding projects is the key to success, and careful site‐specific interpretations will help achieve the aims of rewilding.

Spatial cost–benefit analysis of blue restoration and factors driving net benefits globally - Phoebe J. Stewart‐Sinclair; Carissa J. Klein; Ian J. Bateman; Catherine E. Lovelock (Conservation Biology, 2021)
Marine coastal ecosystems, commonly referred to as blue ecosystems, provide valuable services to society but are under increasing threat worldwide due to a variety of drivers, including eutrophication, development, land‐use change, land reclamation, and climate change. Ecological restoration is sometimes necessary to facilitate recovery in coastal ecosystems. Blue restoration (i.e., in marine coastal systems) is a developing field, and projects to date have been small scale and expensive, leading to the perception that restoration may not be economically viable. We conducted a global cost–benefit analysis to determine the net benefits of restoring coral reef, mangrove, saltmarsh, and seagrass ecosystems, where the benefit is defined as the monetary value of ecosystem services. We estimated costs from published restoration case studies and used an adjusted‐value‐transfer method to assign benefit values to these case studies. Benefit values were estimated as the monetary value provided by ecosystem services of the restored habitats. Benefits outweighed costs (i.e., there were positive net benefits) for restoration of all blue ecosystems. Mean benefit:cost ratios for ecosystem restoration were eight to 10 times higher than prior studies of coral reef and seagrass restoration, most likely due to the more recent lower cost estimates we used. Among ecosystems, saltmarsh had the greatest net benefits followed by mangrove; coral reef and seagrass ecosystems had lower net benefits. In general, restoration in nations with middle incomes had higher (eight times higher in coral reefs and 40 times higher in mangroves) net benefits than those with high incomes. Within an ecosystem type, net benefit varied with restoration technique (coral reef and saltmarsh), ecosystem service produced (mangrove and saltmarsh), and project duration (seagrass). These results challenge the perceptions of the low economic viability of blue restoration and should encourage further targeted investment in this field.

Seagrass Restoration Is Possible: Insights and Lessons From Australia and New Zealand - Yi Mei Tan; Oliver Dalby; Gary A. Kendrick; John Statton; Elizabeth A. Sinclair; Matthew W. Fraser; Peter I. Macreadie; Chris L. Gillies; Rhys A. Coleman; Michelle Waycott; Kor-jent van Dijk; Adriana Vergés; et al. (Frontiers in Marine Science, 2020)

Ancient chromosomal rearrangement associated with local adaptation of a postglacially colonized population of Atlantic Cod in the northwest Atlantic - Marion Sinclair‐Waters; Ian R. Bradbury; Corey J. Morris; Sigbjørn Lien; Matthew P. Kent; Paul Bentzen (Molecular Ecology, 2018)
Intraspecific diversity is central to the management and conservation of exploited species, yet knowledge of how this diversity is distributed and maintained in the genome of many marine species is lacking. Recent advances in genomic analyses allow for genome‐wide surveys of intraspecific diversity and offer new opportunities for exploring genomic patterns of divergence. Here, we analysed genome‐wide polymorphisms to measure genetic differentiation between an offshore migratory and a nonmigratory population and to define conservation units of Atlantic Cod ( Gadus morhua ) in coastal Labrador. A total of 141 individuals, collected from offshore sites and from a coastal site within Gilbert Bay, Labrador, were genotyped using an ~11k single nucleotide polymorphism array. Analyses of population structure revealed strong genetic differentiation between migratory offshore cod and nonmigratory Gilbert Bay cod. Genetic differentiation was elevated for loci within a chromosomal rearrangement found on linkage group 1 ( LG 1) that coincides with a previously found double inversion associated with migratory and nonmigratory ecotype divergence of cod in the northeast Atlantic. This inverted region includes several genes potentially associated with adaptation to differences in salinity and temperature, as well as influencing migratory behaviour. Our work provides evidence that a chromosomal rearrangement on LG 1 is associated with parallel patterns of divergence between migratory and nonmigratory ecotypes on both sides of the Atlantic Ocean.

Imaging the interaction of roots and phosphate fertiliser granules using 4D X-ray tomography - Sharif Ahmed; Trudy Naugler Klassen; Samuel Keyes; Michael Daly; David L. Jones; Mark Mavrogordato; Ian Sinclair; Tiina Roose (Plant and Soil, 2016)